Studies on xanthine oxidase inhibitory activity of Plumeria rubra Linn flower / Siti Sarwani Putri Mohamed Isa - Siti Sarwani Putri , Mohamed Isa (2017)
Plumeria rubra Linn is locally known in Malaysia as “kemboja” and belongs to family Apocynaceae. It has been used traditionally in Southeast Asia for the treatment of malaria, diabetes, analgesic to relieve fever and alleviate arthritis. The Thin Layer Chromatography (TLC) profile of PR ̶ HE, PR ̶ CE, PR ̶ ME and PR ̶ WE extracts of showed the presence of essential oils, phenols, flavonoids and terpenoids. The analysis red flowers extracts with LCMS/MS displayed that it contains 3 ̶ caffeyolquinic acid, 5 ̶ caffeoquinic acid, 1,3 ̶ dicaffeoquinic acid, chlorogenic acid, citric acid, 3,3 ̶ di ̶ O ̶ methylellagic acid, kaempferol ̶ 3 ̶ O ̶ glucoside, kaempferol ̶ 3 ̶ rutinoside, kaempferol, quercetin 3 ̶ O ̶ α ̶ L ̶ arabinopyranoside, quercetin, quinic acid and rutin. The TPC and TFC contents were highest in PR-ME extract at 184.632 mg GAE/g and 203.2.2 mg QE/g, respectively. In the six different antioxidant activity assays, PR ̶ ME extract exhibited the best DPPH scavenging activity at IC50 value at 59.385 μg/ml, highest reducing power toward ferric ions which was 4.950 mmol Fe2+/g extract, highest metal chelating activity at IC50 value at 185.559 μg/mL, highest in hydrogen peroxide scavenging activity at IC50 value at 248.376μg/mL, highest in nitric oxide scavenging activity at IC50 value at 62.096 μg/mL and also highest in superoxide radical scavenging activity at IC50 value at 54.773 μg/mL. The result of XO inhibitory activity in vitro assay revealed that the PR ̶ ME extract possesses highest inhibition effects with the IC50 value was 23.91 μg/mL. The acute toxicity test among the males and females rats demonstrated the PR ̶ ME extract were safe up to a maximum dose of 4000 mg/kg body weight due to no mortality and sign of toxicity occurred within two weeks of experiment. Administration of PR ̶ ME extract at doses of 400 and 200 mg/kg to the rats significantly reduced serum uric acid level by 67.5 % and 28.9 %, respectively when compared to gout control group. Furthermore, the significant inhibitory actions on the XO activity in serum were showed at doses at 400 and 200 mg/kg in which were 7.18 mU/mL by 43.77 % and 8.73 mU/mL by 31.64 %, respectively. The result of in vivo study indicated that serum XO activity was correlated with liver XO activity. XO activity in liver was significantly inhibited by PR ̶ ME extract at doses of 400 and 200 mg/kg, which were 7.76 mU/mL by 31.64 % and 9.88 mU/ml by 16.06 %, respectively. However, PR ̶ ME extract did not show any XO inhibition effects in normal rats. Moreover, no significant difference of body weight between treated rats and nontreated rats within 7 days of extract administration. In conclusion, PR ̶ ME extract from P. rubra red flower contained active phytochemical compounds as detected in LCMS/MS has contributed to inhibition of XO activity in in vitro and in vivo which also had partly mediated to the urate lowering effects in serum as well as the potential to scavenged free radical intermediates and superoxide byproducts.